ANALYSIS OF REMEDIAL ACTIONS DESIGNED TO STABILIZE A HIGHWAY CUT IN A LANDSLIDE AREA - Peter Turček; Monika Šúl'ovská; Miloslav Kopecký; Jakub Panuška (Acta Polytechnica CTU Proceedings)
The Carpathian flysch is widely recognized as a geological environment prone to slope movements. This fragility in such an environment is due to its complicated geological and hydrogeological conditions. Weakened slip surfaces (developed in clay like material), in combination with present or past tectonic activity and difficult hydrogeological conditions with aquifers under pressure, are the main causes of slope movements. The article proposes to analyze the design of remedial action in a landslide area near Žilina. Slip surfaces and water conditions are assumed regarding present geotechnical monitoring. Deep cut with two rows of pile walls is analyzed by the limit equilibrium method and finite element analysis. Interaction between two walls and the effect of an amount of volume of sliding mass on resultant earth pressures and anchor forces were studied. The results from finite element analysis are compared with analytical calculations and the differences are discussed.